Free higher education in South Africa: The funding issue - de Jager, E. (South African Journal of Higher Education, 2026)
In 2015, students have been protesting and demanding free higher education in South Africa (Cloete 2015). It was described as the most intense and violent student protests in a century of higher education (Jansen and Walters 2019). Students were raising their concerns regarding the inequalities in access to higher education, mainly due to the persistent increase in tuition fees which affected the majority of students adversely as they are from less privileged households (Oyekaba 2016). High tuition fees serve as a barrier of entry for many students into the higher education system and achieving a tertiary qualification causes the loss of opportunity to a higher quality of life (Statistics South Africa 2015). It was evident that these demands were urgent as government intervention was needed to find a sustainable solution (Timeslive 2017). After these protests, known as #FeesMust Fall, the president of South Africa, Jacob Zuma, established the Heher Commission of Inquiry to determine the feasibility of higher education together with the viability of the government to finance free higher tuition (Timeslive 2017). The measurements to be put in place would need to resolve the vicious cycle of poverty and unemployment (Timeslive 2017). President Zuma stated that the levels of income inequality in the country is entranced and can be resolved if higher education is accessible to the youth (TimesLive 2017b). The aim of the South African government is to promote an effective and efficient university education system and to support higher education institutes financially (National Treasury 2016). However, government subsidy to the higher education sector has been declining the past few years (Buku 2018). Thus, uncertainty exists regarding whether funding for free higher education is sustainable by the South African government (Lepule 2018). It is noted in a study by Mckay, Naidoo and Simpson (2018) that South Africa’s demand for funding far exceeds the supply and it was also found that the entire process of providing funding is complex. In light of this background, the purpose of this paper is to gain an understanding of what the perceptions are of economic students regarding the funding of free higher education. Another aim is to explore alternative solutions rather than just demanding free higher education as the solution to gain equal access to higher education.